Exploring Mg decorated antimonene for promising hydrogen storage material: A DFT outlook. (July 2023) - Khan, Muhammad Isa; Zaigam, Syeda Masooma; Majid, Abdul; Nabi, Ghulam; Tahir, Muhammad Bilal
Abstract: The adsorption mechanism of a hydrogen molecule on a 2D buckled Antimonene (Sb) monolayer decorated with four Mg atoms was studied using first-principles density functional theory calculations. The four Mg atoms are equally dispersed and fairly ornamented on the surface of the Sb monolayer, with a trend of rising binding energies of 0.12 eV, 0.32 eV, 0.63 eV, and 1.03 eV, respectively. This binding energy is equivalent to 2.1 eV overall. The adsorption energies (hydrogen storage capacity) were increased by increasing the hydrogen molecules up to 20 and remained in the optimal range of 2.7 eV to −6.4 eV (0.68 wt % to 8.4 wt %) on the 4 Mg decorated Sb. The thermodynamics stabilities were confirmed at different high temperatures 400 K–600 K. Different properties were calculated and discussed in detail to ensure the Mg decorated Sb is an efficient hydrogen storage material. Highlights: Mg decorated Sb appeared as a good candidate for Hydrogen storage applications by first-principles study. The adsorption energy remains between 0.021eV to 0.064 eV upon the adsorption of H2 molecules up to 20. Clusters of 2Mg and 3Mg decorated Sb were studied for H2 storage. The Hydrogen storage capacity of Mg- decorated Sb was found as 0.7 wt % to 8.4 wt % for 1–20H2 molecules. Desorption temperature provides the thermal stability of Mg decorated Sb with a corresponding number of H2 molecules.